Modeling of critical factors for integrating sustainability with innovation for Indian small- and medium-scale manufacturing enterprises: An ISM and MICMAC approach - Bisma Mannan; Sonal Khurana; Abid Haleem (Cogent Business & Management, 2016)
The growth of any country depends upon the existence of small- and medium-scale enterprises (SMEs). The greater the number of SMEs present in any country, the economy of the country increases in the same proportion. This paper uses the qualitative research technique to study the critical factors which affect the integration of sustainability with innovation taking into account Indian manufacturing SMEs. An ISM approach is applied to establish the interrelationship between the various critical factors. And with the help of Fuzzy Micmac technique, driver dependence power diagraph is created. From our analysis, it has been found that “government regulation” has the highest dominating power which helps in successful execution of integrating sustainability with innovation. Variables “employee nature” and “working culture” have the highest dependence power. The success of these variables depends on the success of the variables below them. Finally, the limitations of using the above techniques are discussed and then the suggestions are made for the further research.
Keywords: 650